Challenges of Tough Love: Examining San Francisco's Community Justice Center and Evaluating Its Prospects for Success - Daloz, Todd W. (2008)
Decaying urban neighborhoods are a reality in cities across the United States. As various local governments work to improve the quality of life for the residents of such areas through increased law enforcement, many have come up against the limitations of the criminal justice system as a tool for change. This note examines the history and challenges of quality-of-life ordinances and the growth and development of community courts as a reaction to ineffective urban courts and as a structure for enabling change. The author focuses specifically on the new community justice center in San Francisco and offers an assessment of its future prospects